Mediterráneo - Salvatores, Gabriele ([Madrid] [Producciones JRB], 1990)
Greek Sea, World War II. An Italian ship leaves a handful of soldiers in a little island; their mission is to spot enemy ships and to hold the island in case of attack. The village of the
Para todos los públicos
Idiomas : castellano e italiano. Subt. : castellano
Diego Abatantuono, Claudio Bigagli, Giuseppe Cederna
Keywords: Películas cinematográficas -- DVD